Searching for sea lice: surveillance to assess environmental infection pressures to model and inform sea lice infestation management - B Rabe; AG Murray; SC Ives; M Moriarty; DJ Morris (Aquaculture Environment Interactions, 2024)
The expansion and development of sustainable salmon aquaculture requires research, innovation and, where necessary, regulation to manage environmental impacts. Sea lice are a key concern for marine salmonid fish aquaculture as these parasites adversely affect farmed and wild salmonids. Reducing the risk of harmful infestation levels requires appropriate data to support modelling and inform adaptive management processes. Throughout their life cycle, sea lice occur as either planktonic larvae or as ectoparasites on farmed, wild or sentinel fish host populations. Limited resources require surveillance methodologies and strategies for these stages to be optimized to obtain data that meet the specific needs of control. In this review we assess the different surveillance strategies available to inform the appropriate management of sea lice impacts on wild salmonids. We advocate modelling as the most effective way to use surveillance data, with subsequent model improvements informed by the continued input of collected data. A feedback loop is proposed of identifying/collecting empirical data to improve models, which in turn will direct more focused surveillance for future data collection and so drive adaptive management processes. In the future, surveillance monitoring, as part of an adaptive management regime in Scotland, should build on existing links between stakeholders and policy makers, and use both models and data to help the sustainable development of the aquaculture industry.